Expression of Two Major Chitinase Genes of Trichoderma atroviride (T. harzianum P1) Is Triggered by Different Regulatory Signals - Mach, Robert L. (American Society for Microbiology, 1999)
Regulation of the expression of the two major chitinase genes, ech42 (encoding the CHIT42 endochitinase) and nag1 (encoding the CHIT73 N-acetyl-β-d-glucosaminidase), of the chitinolytic system of the mycoparasitic biocontrol fungus Trichoderma atroviride (= Trichoderma harzianum P1) was investigated by using a reporter system based on the Aspergillus niger glucose oxidase. Strains harboring fusions of the ech42 or nag1 5′ upstream noncoding sequences with the A. niger goxA gene displayed a glucose oxidase activity pattern that was consistent under various conditions with expression of the native ech42 and nag1 genes, as assayed by Northern analysis. The expression product of goxA in the mutants was completely secreted into the medium, detectable on Western blots, and quantifiable by enzyme-linked immunosorbent assay. nag1 gene expression was triggered during growth on fungal (Botrytis cinerea) cell walls and on the chitin degradation product N-acetylglucosamine. N-Acetylglucosamine, di-N-acetylchitobiose, or tri-N-acetylchitotriose also induced nag1 gene expression when added to mycelia pregrown on different carbon sources. ech42 expression was also observed during growth on fungal cell walls but, in contrast, was not triggered by addition of chitooligomers to pregrown mycelia. Significant ech42 expression was observed after prolonged carbon starvation, independent of the use of glucose or glycerol as a carbon source, suggesting that relief of carbon catabolite repression was not involved in induction during starvation. In addition, ech42 gene transcription was triggered by physiological stress, such as low temperature, high osmotic pressure, or the addition of ethanol. Four copies of a putative stress response element (CCCCT) were found in the ech42 promoter.